Lemmus trimucronatus AY ... - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Canadian Lemming Lemmus trimucronatus (Richardson, 1825) Type locality: Point Lake, 65.2523°N, 113.1862°W, Mackenzie District, Northwest Territories, Canada [cytb sequence of a topotype: AY219162] (Miller & Kellogg 1955; Fedorov et al. 2003). Synonyms: Arvicola (Lemmus) helvolus Richardson, 1828 [TL: Near headwaters of one of southern tributaries of Peace River, or between there and Jasper House region, Alberta, Canada] (Miller & Kellogg 1955). Distribution: Nearctic species, the range of which covers northern North America from the eastern edge of Alaska through Yukon and Northwest Territories to Nunavut (Fedorov et al. 2003). Comments: Previously, this name was applied to both species-level clades of this species complex (Fedorov et al. 2003), and Lemmus trimucronatus was thought to occur in eastern Russia (Fedorov et al. 2003; Wilson & Reeder 2005; Abramson et al. 2008; Wilson et al. 2017; Abramson & Petrova 2018; Abramson et al. 2018). However, it is a Nearctic species, which, in contrast ... : Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on page 116, DOI: 10.37828/em.2021.40.8, http://zenodo.org/record/13233031 ...